Boron-containing carbon aerogels: excellent mechanical and thermal insulation properties. Issue 1 (1st September 2022) - Mu, Changqing; Cheng, Yiling; Zhang, Kai; Zhou, Jiachang; Fan, Jinpeng
Abstract: The boron-containing carbon aerogels with excellent properties are reported: The precursor of carbon aerogels was modified by boric acid. Compared with the unmodified carbon aerogels, the compressive strength of the prepared carbon aerogels has been significantly improved, reaching 4.57MPa. The density of the carbon aerogels is between 0.253-0.287g/cm 3, and the thermal conductivity is also kept at a low level of 0.057-0.062 (W⋅m -1 ⋅k -1 ). Excellent mechanical and thermal insulation properties make the prepared carbon aerogels have a good application prospect.